Correlation Between Body Mass Index (BMI) and 100 Meter Running Speed of Students of SMP Negeri 20 Makassar - Ramli (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
The level of physical fitness of school students, especially in sprint activities such as the 100-meter run, is often associated with body status as measured by the Body Mass Index (BMI). This study aims to analyze the relationship between BMI and 100-meter running speed in students of SMP Negeri 20 Makassar. This study used a quantitative correlational method with a test and measurement approach to 30 students aged 12–14 years. Data were collected through height and weight measurements to calculate BMI, as well as a 100-meter run test to measure speed. Data analysis using Pearson correlation showed a very significant negative relationship between BMI and running time (r = 0.918, p < 0.001). These results indicate that students with higher BMI tend to have better running speed. This study contributes to the understanding that BMI reflects good physical performance, and suggests a more functional and personalized evaluation of physical fitness. Further research is recommended to involve body composition and other fitness factors.